A rare disease more common than perceived: Two case studies and brief review of IgA Vasculitis - Lydia Shedlofsky DO; Chelsea Crist (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
Immunoglobulin A (IgA) Vasculitis, more commonly known as Henoch-Schönlein Purpura (HSP), is a disorder which causes inflammation and bleeding in the small blood vessels of the skin, joints, intestines, and kidneys. We report 2 cases of IgA vasculitis found in a rural emergency department: 1) HSP in an 8-year-old male who was initially misdiagnosed with insect bites 2) HSP in an adult male patient. We present both cases and a literature review, indicating that low incidence may be secondary to under diagnosis, arguing for a need of further education on the subject.